(3GdaUhd GdegeI aj MUhd GdeJeIs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CbGe CeQ GdOjf HEbGeI GdUdGg hGOGeJgG CeG HYO ajbhd s
(3BNQgG (B:s
(3SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B33s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs